(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
Cirebon waters are one of the areas with dense fishing, industrial and human activities can cause heavy metal pollution in these waters. This study aims to analyze the Hg content in sediments and their relationship with environmental characteristics in three research sites on the Cirebon coast: i.e., Bondet, Sukalila, and Kejawanan. Nine research points were selected at each location. In situ analysis was carried out for temperature, salinity, pH, and DO variables. In addition, surface sediment samples were taken at variations in water depth between 1–6 m. Grain fraction, organic carbon, and heavy metal Hg were analyzed from each of the sediment samples. The results showed that the surface temperature, salinity, pH, and DO of Cirebon waters ranged from 31.09–32.30 oC; 26.4–30.10‰; 7.66–8.56; and 4.50–6.87 mg/L. Cirebon waters are dominated by silt and clay about 1% organic carbon. Mercury in sediments is still considered safe for aquatic life with a concentration of 29.36–68.55 µg/kg-dw. Principal Component Analysis shows that the three study sites have different water characteristics and hence, influence the Hg deposition. Overall, although Hg accumulation occurs, it is ecologically safe for biota life. Sedimentary accumulation of Hg was probably due to the terrestrial input and the condition of environmental deposition such as riverine flow and coastal current.